(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article analyzes women’s life strategies in the context of New Uzbekistan from the perspective of gender equality and sustainable development principles. The study explores the opportunities created for women as a result of legal, social, and economic reforms, their social activity, integration into technological fields, and their role in digital transformation processes. It presents scientifically grounded conclusions regarding key aspects of gender policy, existing problems, and ways to address them.